Series de televisión como una herramienta para la investigación social. Análisis temático, epistemológico y metodológico (2021)
This article is based on the hypothesis that social research using television series as a tool is made without a robust epistemological component, without methodological variety and without thematic breadth. To verify this hypothesis, 36 scientific articles are analyzed that use the following series as a social research tool: Breaking Bad, The X Files, Game of Thrones, I Love Lucy, The Sopranos, Mad Men, Orange is The New Black, Sex and the City, Star Trek and The West Wing. Finally, after working with a base of 648 records, it is concluded that the articles analyzed do have clear epistemological references, a wide methodological range and address a wide variety of topics.